Analiza ryzyka jako element strategii bezpieczeństwa systemu informacyjnego przedsiębiorstwa - Nowicki, Adam; Rot, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Security strategy is a document, which defines the main security aim. It should show in objective way the aims, needs in security area and define the conventional security level. To elaborate the strategy one should conduct initial resources value analysis as well as threats and risk analysis. The risk analysis subject in area of information system management is still an unexamined problem. There are many different approaches, methods, whose aim is to identify and estimate the risk in information systems performance. It is very important process and it is necessary to include it in a process of building IS security strategy in enterprise. The purpose of the article is to present the subject of IS security strategy in a company and to discuss risk analysis as its main component. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 68-82